Revisiting the role of independence formation and organizing individual work of the student in the educational process of HEI - Nurgaliyeva, Murshida; Auyezova, Amina; Kosmuratova, Aitkul (Opción, 2018)
This article considers one of the key problems of modern education, namely the formation of independence as a necessary quality of the student. The very organization of educational process should be built on the principles of independent student activity. It is necessary to reinforce an integral complex of independence in student’s mind. To accomplish this, it is important to organize HEI educational process in such a way that independent work becomes a determining condition for the formation of student’s independence as a subject of learning and activity. Independent work involves digestion, reinforcement and application of knowledge.